Pharmacological management of cardiovascular conditions and diabetes in older adults with HIV infection. Issue 5 (18th December 2013) - Gedela, K; Vibhuti, M; Pozniak, A; Ward, B; Boffito, M
<x xml:space="preserve">Abstract</x> This review looks at the evidence for potential and theoretical risks of combining antiretroviral treatment with drugs prescribed for cardiovascular disease and diabetes. These conditions are common in the HIV‐infected population as a result of ageing and the increased risk associated with both HIV infection and antiretroviral intake.